Water column raw data (Kongsberg EM 122 entire dataset) of RV SONNE during cruise SO309 - Evgenia A Bazhenova; Sam Davidson; Alissa Bach; Dierk Hebbeln; André Freiwald (PANGAEA, 2025)
Raw water column data were collected using the ship extquotesingles own Kongsberg EM 122 multibeam echosounder during the RV SONNE cruise SO309 CoralNewZ (Cold-water Coral Biology & Geology off Aotearoa New Zealand). The cruise took place between 2025-01-16 and 2025-02-15 (Wellington to Wellington, New Zealand). The primary goal was to search for cold-water coral communities and mounds in the EEZ of New Zealand. Hydroacoustic team included Sam Davidson (NIWA), who was funded by the NIWA internal project OCN2503 – NIWA Strategic Voyage Fund. Bathymetry and backscatter data were recorded using the EM122 deep-water echosounder within 2 main working areas: East of Stewart Island and Chatham Rise (both Pacific Ocean), as well as alone the transits within the EEZ of New Zealand. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Sound velocity profiles (SVP) were regularly collected in all the main working areas and are part of this dataset. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).